Pengaruh Kualitas Layanan Terhadap Minat Beli Ulang di Restoran Mie Gacoan Kota Bandung - Dewi Sri Sulastri (International Journal Administration, Business & Organization, 2022)
The purpose of this study is to find the effect of service quality on repurchase interest in the city of Bandung. The sample used in this study amounted to 139 respondents who are consumers who buy food at Mie Gacoan Restaurant in Bandung City. This research uses descriptive analysis method, validity and reliability test, correlation analysis and simple regression analysis. Data was collected through questionnaires distributed through social media to respondents who met the criteria. The results showed that the quality of service at Mie Gacoan Restaurant had an influence but the effect obtained was not significant on consumer repurchase interest. This means that service quality is not strong enough to influence consumer repurchase interest in Mie Gacoan Bandung restaurant. In the study, the results obtained were 23.8% the effect of service quality on repurchase interest. Meanwhile, 76.2% is influenced by other variables not discussed in this study.